2013
DOI: 10.1016/j.neurobiolaging.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of zinc-deficient human superoxide dismutase in Drosophila neurons produces a locomotor defect linked to mitochondrial dysfunction

Abstract: More than 130 different mutations in the Cu/Zn superoxide dismutase (SOD1) gene have been associated with Amyotrophic lateral sclerosis (ALS) but the mechanism of this toxicity remains controversial. To gain insight into the importance of the zinc site in the pathogenesis of SOD1 in vivo, we generated a Drosophila model with transgenic expression of a zinc-deficient human SOD1. Expression of zinc-deficient SOD1 in Drosophila resulted in a progressive movement defect with associated mitochondrial cristae vacuol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
(63 reference statements)
1
26
0
1
Order By: Relevance
“…In agreement with other studies333435363738 our results point to a possible link between SOD1, mitochondrial dysfunction and ALS. Intriguingly, we showed that the over-expression of the wild type hSOD1 also causes mitochondrial alterations.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies333435363738 our results point to a possible link between SOD1, mitochondrial dysfunction and ALS. Intriguingly, we showed that the over-expression of the wild type hSOD1 also causes mitochondrial alterations.…”
Section: Discussionsupporting
confidence: 93%
“…Zinc also contributes to neuronal death in hypoxic-ischemic injury (34,35,(47)(48)(49) by interfering with mitochondrial and metabolic functions (50,51), altering ion fluxes (52), and other mechanisms (53). Abnormalities in zinc homeostasis may be important in chronic neurodegenerative diseases, such as Alzheimer's (54) and amyotrophic lateral sclerosis (55)(56)(57), and have been shown to play a key role in oxidative stress-induced death in neurons and oligodendrocytes (58,59). Given the abundant evidence for the importance of zinc in acute and chronic neurodegeneration, we have investigated its involvement in the death of RGCs following optic nerve injury.…”
Section: Significancementioning
confidence: 99%
“…ALS-associated mutations can hinder binding of SOD1protein to zinc ions, resulting in cellular toxicity (Crow et al, 1997;Lyons et al, 1996). Recently, researchers using transgenic Drosophila expressing zinc-deficient hSOD1 obtained evidence supporting a link between mutant SOD1 and mitochondrial dysfunction (Bahadorani et al, 2013). These flies harbored a D83S mutation in a zinc-binding domain of exon 4 that inhibits binding of SOD1 protein to zinc, without affecting binding to its other cofactor, copper.…”
Section: 0 Drosophila Models Of Alsmentioning
confidence: 99%